2008
DOI: 10.1523/jneurosci.5366-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Spectrotemporal Processing Differences between Auditory Cortical Fast-Spiking and Regular-Spiking Neurons

Abstract: Excitatory pyramidal neurons and inhibitory interneurons constitute the main elements of cortical circuitry and have distinctive morphologic and electrophysiological properties. Here, we differentiate them by analyzing the time course of their action potentials (APs) and characterizing their receptive field properties in auditory cortex. Pyramidal neurons have longer APs and discharge as regular-spiking units (RSUs), whereas basket and chandelier cells, which are inhibitory interneurons, have shorter APs and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
73
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 95 publications
(127 reference statements)
8
73
1
Order By: Relevance
“…Previously, we have shown that parameters that describe the stimulus-based content of receptive fields (e.g., characteristic frequency, excitatory bandwidth, envelope modulation preferences) are relatively independent of parameters that describe how the processing is accomplished (e.g., receptive field separability, feature selectivity, nonlinearity structure) (22). A factor analysis revealed potential interdependences among variables that characterize how spectrotemporal stimuli are processed.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Previously, we have shown that parameters that describe the stimulus-based content of receptive fields (e.g., characteristic frequency, excitatory bandwidth, envelope modulation preferences) are relatively independent of parameters that describe how the processing is accomplished (e.g., receptive field separability, feature selectivity, nonlinearity structure) (22). A factor analysis revealed potential interdependences among variables that characterize how spectrotemporal stimuli are processed.…”
Section: Resultsmentioning
confidence: 92%
“…However, neuronal stimulus preferences change widely across the tonotopic array, e.g., stimulus binaurality, bandwidth, or intensity, complicating a population analysis of general processing aspects (9,10,34). Here, we focus on layer-dependent auditory processing principles (''how'') that are largely independent from the stimulus content (''what'') (22).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the duration of extracellularly recorded spike waveforms is directly related to the duration of intracellularly recorded waveforms (Henze et al, 2000;Gold et al, 2006), narrow-spiking (NS; putative interneurons) and broad-spiking neurons (BS; putative pyramidal cells) can also be discriminated with extracellular recording techniques. This approach has proven successful in several studies in the somatosensory (Simons, 1978;McCormick et al, 1985;Swadlow and Gusev, 2002), visual (Swadlow and Weyand, 1987;Gur et al, 1999;Shapley et al, 2003;Mitchell et al, 2007;Nowak et al, 2008), auditory (Atencio and Schreiner, 2008), and prefrontal cortices (Wilson et al, 1994;Rao et al, 1999;Constantinidis and Goldman-Rakic, 2002) of different mammalian species.…”
Section: Introductionmentioning
confidence: 99%